DEVELOPING ORDER AND CUSTOM PRODUCTION INFORMATION SYSTEM WITH ORDER TRACKING SYSTEM IN BATIK BALQIS COLLECTION - Carlina, Selvi; Ayundyayasti, Prima (KEUNIS, 2021)
Batik Balqis Collection is a boutique and batik producer that most of the goods are self-produced. In conducting their business, Batik Balqis Collection provides services in the form of custom orders that are still carried out manually, so it is difficult to describe the details of the order design and inaccuracies in calculating the cost of goods manufactured for each order. This research aims to design and develop order and custom production information systems with tracking information for Batik Balqis Collection customers. The method used to develop the system is the Prototype method. The prototype method phase consists of initial requirement, design, prototyping, customer evaluation, review and update, system development, and system implementation. Data collection methods used are interviews and observation. The system's outputs are purchase report, order report, material inventory report, work in process inventory report, finished good inventory report, and cost of goods manufactured report. By implementing this system, users are expected to run their business processes more efficiently.